Unexpected Ethical Dilemmas in Sex Assignment in 46,XY DSD due to 5-alpha Reductase Type 2 Deficiency - Byers, Heather M. (Am J Med Genet C Semin Med Genet, 2017)
Sex assignment at birth remains one of the most clinically challenging and controversial topics in 46,XY disorders of sexual development (DSD). This is particularly challenging in deficiency of 5-alpha reductase type 2 given that external genitalia are typically undervirilized at birth but most individuals virilize at puberty to a variable degree. Historically, most individuals with 5-alpha reductase deficiency were raised females. However, reports that over half of patients who underwent a virilizing puberty adopted an adult male gender identity have challenged this practice. Consensus guidelines on assignment of sex of rearing at birth are equivocal or favor male assignment in the most virilized cases. While a male sex of rearing assignment may avoid lifelong hormonal therapy and/or allow the potential for fertility, female sex assignment may be more consistent with external anatomy in the most severely undervirilized cases. Herein, we describe five patients with 46,XY DSD due 5-alpha-reductase type 2 deficiency, all with a severe phenotype. An inter-disciplinary DSD medical team at one of two academic centers evaluated each patient. This case series illustrates the complicated decision-making process of assignment of sex of rearing at birth in 5-alpha reductase type 2 deficiency and the challenges that arise when the interests of the child, parental wishes, recommendations of the medical team and state law collide.